Hypocenter Relocation of Volcanic Earthquake at Agung Vulcano - Reni Agustiani; Bagus J. Santosa; Yasa Suparman; Devi K. Syahbana; Gazali Rachman (IPTEK Journal of Proceedings Series, 2019)
Agung Volcano is a stratovolcano located in the area of Karangasem regency of Bali and is in the northwest-southeast fault alignment with Batur, Abang and Seroja Volcano. The existence of this alignment allegedly related to the fracture in the northwest of the island of Bali. The eruption of Agung Volcano recorded on November 25th, 2017 was a significant danger for people living around it. Therefore, it is necessary to monitor the activity of Agung Volcano. The method used in this study is the relocation of volcanic earthquake sources to determine the location of the source of the earthquake which caused an increase in Mount activity. Hypocenter relocation was carried out on 138 earthquake events during October 2017-January 2018 using the Coupled Velocity-Hypocenter method. Hypocenter was obtained at a depth of less than 10 km under sea level with an RMS value <0.3 seconds, and this is thought to have a flow of magma fluid through the conduit which moves towards the earth's surface and triggers an eruption